Piauí in the independence process: contribution to Empire Building in 1823 - de Araújo, Johny Santana (2015)
This paper search to explore how happened the conducting of the independence process in Piauí in 1823. Three elements are essential to the reconstitution of this narrative, the first is the importance of the region for the maintenance Portuguese colonial empire in America. In second place the intense mobilization social and military political which are foundations for the understanding of a national discourse which was molded some years later, and ultimately the forwarding given to the prominent figures in this process, personified by the different ways followed by actors political in the post-independence.